2006
DOI: 10.1002/nur.20133
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying work–family conflict among registered nurses

Abstract: Work-family conflict is challenging for nurses and the nursing profession. Still unclear is how frequently nurses experience work-family conflict and which nurses experience it most frequently. We document the prevalence and frequency of work-family conflict and describe the demographic predictors of frequent work-family conflict. Nurses reported greater work interference with family than family interference with work. Fifty percent of nurses reported chronic work interference with family (occurring at least o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
185
6
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(211 citation statements)
references
References 39 publications
11
185
6
9
Order By: Relevance
“…Nurses have been shown to have considerable more problems with work interfering with home life, than the other way around 9 . This coincides with a study showing how females to a larger extent than men, tend to carry work stress into home life 29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses have been shown to have considerable more problems with work interfering with home life, than the other way around 9 . This coincides with a study showing how females to a larger extent than men, tend to carry work stress into home life 29 .…”
Section: Introductionmentioning
confidence: 99%
“…This coincides with a study showing how females to a larger extent than men, tend to carry work stress into home life 29 . Nurses are a mostly female population, and it has been argued that work-to-family conflict is the foremost construct of interest in these workers 9 .…”
Section: Introductionmentioning
confidence: 99%
“…This increase may have contributed to a growth in female participation in the labor market, traditionally involving a double responsibility of tasks, i.e., tasks related to work and those related to the home, including, among other things, caring for children [11]. In addition, the demands of work may cause adverse effects that manifest themselves in terms of the physical and psychological health of individuals, including tiredness, stress, insomnia, and depression, all of which can cause an emotional and relational deterioration between parent and child, especially for school-age children who are most affected by school failure [12][13][14]. On the Fig.…”
Section: Personal Factors and Work-family Balancementioning
confidence: 99%
“…WFB is a phenomenon that is ideally observed in a work-family relationship and has led to the emergence of a new research stream. Research on WFB can be characterised as being organised along competing positive and negative perspectives [2][3][4]. Previous studies have assumed a 'win-lose' relationship between family and work by focusing on the work-family conflict based on individuals who have limited time and resources to allocate to their many life roles [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have assumed a 'win-lose' relationship between family and work by focusing on the work-family conflict based on individuals who have limited time and resources to allocate to their many life roles [5]. Other studies [3][4][5][6] have reported that WFB is pursued to resolve the work-family conflict, which can be regarded as the opposite of WFB.…”
Section: Introductionmentioning
confidence: 99%